MANAJEMEN KOMUNITAS OPTIMUM PADA KELOMPOK SWADAYA MASYARAKAT BIDANG SANITASI DI KAMPUNG BUSTAMAN, KELURAHAN PURWODINATAN, KECAMATAN SEMARANG TENGAH - Indrayati, Ariyani (Forum Ilmu Sosial, 2012)
Self Supporting Community Group of Sanitation in Bustaman Kampong, Semarang City, at the beginning only control their activity to manage their Public Toilet. But in additional time, they have advance activity to developed biogas as alternative energi at their kampong. This community group developed their organization after got intervention from ones of Non Governmental Organisation (BORDA, Germany) and share their knowledge, skill, and ability of capacity building to develop their organisation. There are some factors that influence the community group become increasing their ability and capacity building. That factors can be classificated in to two main group that called eksternal factors and internal factors. The determinan factor of eksternal is introduction from other institution like from NGO. The second factor is internal factor that consist of local leadership, human resource up-grading and the rising of community awareness to suistainable management.